Optimal taxation and social insurance in a lifetime perspective - Ary Lans Bovenberg; Peter Birch Sørensen (Center for Economic Studies and ifo Institute (CESifo), 2006)
Advances in information technology have improved the administrative feasibility of redistribution based on lifetime earnings recorded at the time of retirement. We study optimal lifetime income taxation and social insurance in an economy in which redistributive taxation and social insurance serve to insure (ex ante) against skill heterogeneity as well as disability risk. Optimal disability benefits rise with previous earnings so that public transfers depend not only on current earnings but also on earnings in the past. Hence, lifetime taxation rather than annual taxation is optimal. The optimal tax-transfer system does not provide full disability insurance. By offering imperfect insurance and structuring disability benefits so as to enable workers to insure against disability by working harder, social insurance is designed to offset the distortionary impact of the redistributive labor income tax on labor supply.
Keywords: H21; H55; 330; optimal lifetime income taxation; optimal social insurance; Einkommensteuer; Optimale Besteuerung; Sozialversicherung; Erwerbsunfähigkeit; Ökonometrisches Modell